Anthropogenic drying in central-southern Chile evidenced by long-term observations and climate model simulations - Juan P. Boisier; Camila Alvarez-Garretón; Raúl R. Cordero; Alessandro Damiani; Laura Gallardo; René D. Garreaud; Fabrice Lambert; Cinthya Ramallo; Maisa Rojas; Roberto Rondanelli (Elementa: Science of the Anthropocene, 2018)
The socio-ecological sensitivity to water deficits makes Chile highly vulnerable to global change. New evidence of a multi-decadal drying trend and the impacts of a persistent drought that since 2010 has affected several regions of the country, reinforce the need for clear diagnoses of the hydro-climate changes in Chile. Based on the analysis of long-term records (50+ years) of precipitation and streamflow, we confirm a tendency toward a dryer condition in central-southern Chile (30–48°S). We describe the geographical and seasonal character of this trend, as well as the associated large-scale circulation patterns. When a large ensemble of climate model simulations is contrasted to observations, anthropogenic forcing appears as the leading factor of precipitation change. In addition to a drying trend driven by greenhouse gas forcing in all seasons, our results indicate that the Antarctic stratospheric ozone depletion has played a major role in the summer rainfall decline. Although average model results agree well with the drying trend’s seasonal character, the observed change magnitude is two to three times larger than that simulated, indicating a potential underestimation of future projections for this region. Under present-day carbon emission rates, the drying pathway in Chile will likely prevail during the next decades, although the summer signal should weaken as a result of the gradual ozone layer recovery. The trends and scenarios shown here pose substantial stress on Chilean society and its institutions, and call for urgent action regarding adaptation measures.